Webcam Untuk Sistem Pemantauan Menggunakan Metode Deteksi Gerakan - Kartika Firdausy; Daryono Daryono; Anton Yudhana (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
Recently, numerous daily activities force people to leave their home more often. This situation oftentriggers crimes. Slow handling and lack of anticipation cause the number of crimes increases. Therefore, amonitoring mechanism is needed to improve the security and as an anticipation to unexpected offenses. Thispaper discusses the design of movement detecting system using webcam to monitor the presence of movingobjects with size of human bodyWebcam Logitech QuickCamTM IM is used to capture the object movement at 30 fps. The actual image iscompared to the previous image. The comparison is done for every 5 frames. The software is written in Pascallanguage. A buzzer type alarm is also included in the system. If the camera captures an image of an object withsize greater than or equal to a threshold value, the alarm will be activated and the system records the objectimages. The system is capable in detecting the movement of objects at effective range of 3.5 m.Key words: movement detection, webcam, monitoring